Exploitation of plants for the removal of organics in environmental remediation - Macek, T; Macková, M; Kás, J (Biotechnology advances, 2000)
This review concentrates on the description of various phytoremediation technologies, paying special attention to removal of organics and the application of in vitro systems for basic research in the role of plants for the remediation of contaminated sites or flows, and in the improvement of their effectiveness. Various aspects of xenobiotic metabolism in plant cells, the role of enzymes involved, and the cooperation with rhizospheric microorganisms accelerating remediation of organics are shown. Application of this approach as well as the possibility of introduction of foreign genes into plant genome that can enhance the rate of the bioremediation are discussed.